Triggering Avoidance: Dissociable Influences of Aversive Pavlovian Conditioned Stimuli on Human Instrumental Behavior - Garofalo, Sara; Robbins, Trevor W. (Frontiers in Behavioral Neuroscience, 2017)
The present study investigates human aversive Pavlovian-to-Instrumental Transfer (PIT) and possible influences of outcome devaluation and instrumental overtraining on this effect. PIT measures the extent to which a Pavlovian conditioned stimulus can increase instrumental responses independently paired with the same (outcome-specific transfer) or a different (general transfer) reinforcer. Two measures of PIT were obtained: the percentage of instrumental responses and the vigor of such responses. Thirty-eight volunteers performed a standard PIT task sequence. Results showed a double dissociation between outcome-specific and general transfer: the first selectively expressed in the amount of responses, the second in the vigor measure solely. Furthermore, outcome-specific transfer was enhanced by overtraining, but not affected by devaluation. General transfer, on the other hand, was affected by neither overtraining, nor devaluation. A positive correlation between general transfer and sensitivity to punishments was found. Findings are discussed in terms of hypothetically different underlying neurobehavioral mechanisms and their relations to habits and goal-directed behavior.